Money and sustainability : the missing link : a report from the Club of Rome-EU Chapter to Finance Watch and the World Business Academy - Lietaer, Bernard A., ....-; Club of Rome. EU Chapter (Axminster, Devon, United Kingdom : Triarchy Press, 2012)
Bernard Lietaer, author, financial expert, and co-designer of the ECU (the monetary mechanism that later became the euro) presented compelling arguments to show that there is a structural flaw in the current monetary system that generates all the current problems and repeated financial and monetary crises, including the eurozone crisis. It is also ecologically unsustainable as it encourages climate change and over-consumption. Mr Lietaer presented his arguments during a lecture, hosted by the Club of Rome's EU Chapter in Brussels, to launch the Report from Club of Rome: Money and Sustainability: the Missing Link.
Includes bibliographical references (p. 199-209).
Keywords: Duurzaamheid; Economic stabilization; Geld; Monetary policy